2017
DOI: 10.1259/bjr.20160804
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous radiofrequency ablation of hepatocellular carcinoma in cirrhosis: analysis of complications in a single centre over 20 years

Abstract: RFA of HCC in patients with cirrhosis is safe, even in case of invasion of the portal venous system. Functional liver reserve should be strictly monitored, mainly when pre-RFA total bilirubin value is >2.5 mg dl. The study was approved by our institutional review board. Advances in knowledge: The total bilirubin value >2.5 mg dl represents the main marker of functional liver reserve that predicts decompensation of liver cirrhosis in patients undergoing RFA for HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 20 publications
(25 reference statements)
1
14
0
Order By: Relevance
“…In RFA, an electrical current is delivered to the tumor tissue through a needle electrode under imaging guidance and causes heat-based thermal cytotoxicity. [46] However, complications associated with RFA also occur during thermal injury. Although most of these complications are usually minor and self-limited, major complications may be fatal in cases in which diagnosis and treatment are delayed and inappropriate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In RFA, an electrical current is delivered to the tumor tissue through a needle electrode under imaging guidance and causes heat-based thermal cytotoxicity. [46] However, complications associated with RFA also occur during thermal injury. Although most of these complications are usually minor and self-limited, major complications may be fatal in cases in which diagnosis and treatment are delayed and inappropriate.…”
Section: Discussionmentioning
confidence: 99%
“…RFA is the most widely used 1st-line treatment in selective patients with HCC and metastatic liver cancer and is usually safe and well tolerated. [46] However, previous studies reported the occurrence of major complications associated with RFA, including hemorrhage, liver abscess, hepatic infarction, bile duct injury, gastrointestinal perforation, hemothorax, pneumothorax, tumoral seeding, and hepatic failure. [710] The rates of major complications and mortality associated with RFA were 4.1% (range: 3.3–5.1) and 0.15% (range: 0.08–0.23), respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with cirrhosis and superimposed ICC with a total bilirubin level >2.5 mg/dL were also excluded. 13,16 Before ablation, all patients underwent clinical and biochemical exams (including assays for Ca 19.9 and alphafetoprotein), abdominal conventional US, contrast-enhanced US (CEUS), CECT and/or CEMRI. Enhancement characteristics were classified into four patterns: peripheral irregular rim-like hyperenhancement (type I); diffuse heterogeneous hyperenhancement (type II); diffuse homogeneous hyperenhancement (type III); and diffuse heterogeneous hypoenhancement (type IV).…”
Section: Methodsmentioning
confidence: 99%
“…Similar rates have been observed in more recent studies [46,47] . A pre-RFA value of bilirubin > 2.5 mg/dL may predict liver decompensation after treatment [48] .…”
Section: Radio Frequency Ablationmentioning
confidence: 99%